Pelatihan Deteksi Dini Stunting Pada Kader Posyandu Pasca Pandemi Covid-19 Di Desa Plumbon, Mojolaban, Sukoharjo - Sukmaningsih, Wahyu Ratri; Habibi, Musta'inul; Wulandari, Novita Sri; Putri, Wella Niki (Universitas Islam Negeri Sumatera Utara, 2024)
The COVID-19 pandemic has had a serious impact on the health of toddlers, especially in increasing the risk of stunting. This community service aims to evaluate the effectiveness of early stunting training on the knowledge and skills of Posyandu cadres after the COVID-19 pandemic in the village of Plumbon, Mojolaban, Sukoharjo. The method of early stunting training is implemented with a participatory approach, involving 34 Posyandu cadres as participants. The training covers stunting prevention topics, including the identification of risk factors, provision of nutritious food, and monitoring child growth. Evaluation is conducted through pretests and posttests as well as direct observation of Posyandu cadre practices. The results show a significant increase in the knowledge and skills of Posyandu cadres after the training. Participants are better able to identify stunting risk factors and provide more comprehensive care for toddlers under Posyandu monitoring. Additionally, the training strengthens the collaboration between Posyandu cadres and the community in efforts to prevent stunting. In conclusion, this community service makes a tangible contribution to enhancing the capacity of Posyandu cadres and reducing the risk of stunting in toddlers in the village of Plumbon, Mojolaban, Sukoharjo. It is recommended to continue and expand similar training programs to other villages as part of sustainable stunting prevention efforts.